(w^-7)^4 = w^-28 or 1/w^28
2007-02-10 16:14:07
·
answer #1
·
answered by leo 6
·
1⤊
1⤋
1. A negative exponent indicates a fraction with the base raised to the abs val of the exponent in the denominator: (u^2)^-4 = u^(2*-4) = u^-8 = 1/(u^8) 2. This one is just pathetic: 6+(-6) = 6-6 = 0, and 0^2=0, so (6+-6)^2=0 Before getting freaked out by a problem that looks difficult, take a good look at it and try to find a way to make it simple. In this case, don't FOIL (6+-6), simplify it first and the problem becomes very easy to do. 3. 30w^2+15x^2+43xw-36w-3x+6
2016-05-25 08:27:30
·
answer #2
·
answered by Heather 3
·
0⤊
0⤋
You really should read the previous answers before you continue asking questions; the answers are all there.
(w^-7)^4 = (1/w^7)^4 = 1^4 / (w^7)^4 = 1/w^28
2007-02-10 16:15:04
·
answer #3
·
answered by Tim P. 5
·
0⤊
0⤋
Simplify: (w^-7)^4
First: when a variable has a negative exponent - make the variable a fraction > place the variable over 1......
(w^-7/1)^4
Sec: rule - exponents have to be positive > place the variable in the denominator....
(1/w^7)^4
Third: distribute the exponent "4" with the terms in parenthesis --- when you have a variable with an exponent raised to another exponent, multiply the exponents.....
(1^4/w^(7*4))
1/w^28
2007-02-10 16:33:29
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
0⤊
2⤋
Since a^-x=1/a^x, you end up with (1/w^7)4. And because (a/b)^x=a^x/b^x, and (a^x)^y=a^(x*y), you get 1^4/w^28. Since 1*1*1*1 is obviously 1, you get 1/w^28. Thus, your answer is 1/w^28.
2007-02-10 16:15:18
·
answer #5
·
answered by CB #7 ftw 3
·
0⤊
0⤋
(1/w^7)^4 = 1/w^28
2007-02-10 16:15:04
·
answer #6
·
answered by Jerry P 6
·
0⤊
0⤋
(w^-7)^4
=w^-28
=1/w^28
2007-02-10 16:14:58
·
answer #7
·
answered by fcas80 7
·
0⤊
1⤋
w^-a = 1/w^a
(w^-7)^4 = w^-28
1/w^28
2007-02-10 16:15:09
·
answer #8
·
answered by radne0 5
·
0⤊
0⤋
1/(w^28)
2007-02-10 16:18:33
·
answer #9
·
answered by ♥Tom♥ 6
·
0⤊
1⤋
Answer withdrawn.
2007-02-10 16:14:42
·
answer #10
·
answered by ecolink 7
·
0⤊
2⤋